Os-based high-temperature amorphous alloy material and preparation method thereof
By designing Os-based high-temperature amorphous alloy materials, including Os, B and a variety of high-modulus elements, and using advanced smelting and preparation technology, the problem of insufficient service temperature of existing amorphous alloy materials is solved, the material requirements of high-temperature glass molding molds are achieved, and excellent mechanical properties are demonstrated.
Patent Information
- Application Number
- CN202411932555.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The service temperature of existing amorphous alloy materials is generally below 600K, and it is difficult to use in the manufacture of high-temperature glass molding molds, and there is a lack of a high-temperature amorphous alloy system with Os as the matrix.
An Os-based high-temperature amorphous alloy material is designed, with the chemical formula of OsaBbMc, which contains Os element, B element and M element (at least one of Zr, Hf, V, Ta, W). The master alloy is prepared by induction smelting and arc smelting, and then a thin band or block of Os-based high-temperature amorphous alloy is prepared by melt quenching or copper mold casting.
It has achieved high glass transition temperature (up to 1283K) and excellent mechanical properties of Os-based high-temperature amorphous alloy materials, which is far superior to existing amorphous alloy materials and is suitable for precision glass forming mold materials.
Smart Images

Figure CN119640162A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of development and preparation of amorphous alloy materials, and in particular relates to an Os-based high-temperature amorphous alloy material and a preparation method thereof. Background Art
[0002] Amorphous alloys are ideal materials for precision glass molding molds due to their unique thermoplastic forming, isotropy, uniform structure, small thermal expansion coefficient, atomic-level surface finish and other characteristics, and have important application prospects in the field of glass molding. The operating temperature of glass molding molds often exceeds 973K (700℃), however, due to the limitations of glass transition temperature, thermal stability, and glass forming ability, the service temperature of traditional amorphous alloys is generally below 600K, making it difficult to use them to manufacture glass molding molds.
[0003] Amorphous alloys with a glass transition temperature exceeding 973K are called high-temperature amorphous alloys, which have incomparable mechanical property advantages over crystalline materials. For example, they have high strength and hardness at room temperature, and still have ultra-high high-temperature strength before the glass transition temperature, which is expected to meet the mold mechanical property requirements in precision manufacturing fields such as optical component compression molding. At present, high-temperature bulk amorphous alloys (glass forming ability ≥ 1mm, glass transition temperature ≥ 973K) that have been developed include ternary systems such as IrNiTa and MoCoB. However, high-temperature bulk amorphous alloy systems with even better performance remain to be developed.
[0004] The design orientation of composition based on high modulus elements is an important means to develop high-strength amorphous alloys. As the pure metal element with the highest modulus, Os, an amorphous alloy system based on it has not yet been developed in the prior art. In addition, the ternary alloy components have a wide range of components. How to quickly screen and obtain alloy components with glass-forming ability, so as to develop new Os-based high-temperature amorphous alloy materials, and then solve the urgent demand for optical glass molding mold materials, and provide key materials and technologies for my country's advanced manufacturing industry, is a technical problem that technicians in this field need to solve urgently. Summary of the invention
[0005] The present invention aims to provide an Os-based high-temperature amorphous alloy material, the chemical formula of which is Os a B b M c , mainly Os (osmium), small atomic element B (boron) as the second element, M element includes at least one of Zr (zirconium), Hf (hafnium), V (vanadium), Ta (tantalum) and W (tungsten). a, b and c are the atomic percentages (at%) of the corresponding elements, a = 39-50, b = 34-44, c = 12-24, and the sum of the atomic percentages of each element is a + b + c = 100.
[0006] In a preferred embodiment, the glass transition temperature of the Os-based high temperature amorphous alloy material is 1040K-1283K.
[0007] In a preferred embodiment, the Vickers microhardness value of the Os-based high temperature amorphous alloy material is above 16.74 GPa.
[0008] The Os-based high-temperature amorphous alloy material provided by the present invention can simultaneously take into account high glass transition temperature and high mechanical properties, and its glass transition temperature can reach 1283K, which is much better than the existing amorphous alloy materials in the prior art. At the same time, its mechanical data such as elastic modulus, maximum Vickers microhardness, room temperature compression fracture strength and compression fracture strength at 1000K are much higher than those of existing amorphous alloy materials.
[0009] In a preferred embodiment, in the Os-based high temperature amorphous alloy material, when the M element is the Hf element, the atomic percentages of the elements are a=42-50, b=34-42, c=12-20, and a+b+c=100.
[0010] In a preferred embodiment, the Os a B b Hf c The glass transition temperature of the high temperature amorphous alloy material is 1231K and the Vickers microhardness is 18.06GPa.
[0011] In a preferred embodiment, the Os 46 B 38 Hf 16 The Young's modulus of the high-temperature amorphous alloy material is 299 GPa, the compressive fracture strength at room temperature is 6.8 GPa, and the compressive yield strength at 1000K is 3.9 GPa.
[0012] In a preferred embodiment, the Os-based high temperature amorphous alloy composition includes Os 45 B 35 Zr 20 , Os 45 B 35 V 20 , Os 50 B 35 Ta 15 and Os 45 B 35 W 20 .
[0013] Another object of the present invention is to provide a method for preparing an Os-based high-temperature amorphous alloy material, which specifically comprises:
[0014] Step 1: According to the chemical formula of the Os-based high temperature amorphous alloy, Osa B b M c Calculate the mass ratio of each element and weigh and mix the ingredients; the element M includes at least one of Zr, Hf, V, Ta and W; a, b and c are the atomic percentages of the corresponding elements, a=39-50, b=34-44, c=12-24, and the sum of the atomic percentages of the elements is a+b+c=100;
[0015] Step 2: using an induction melting method to melt each element into a master alloy ingot;
[0016] Step 3: Heat and melt the master alloy ingot obtained in step 2 in a protective atmosphere, and prepare an Os-based high-temperature amorphous alloy strip by melt spinning; or heat and melt the master alloy ingot obtained in step 2 in a protective atmosphere, and prepare an Os-based high-temperature amorphous alloy block by copper mold casting.
[0017] In a preferred embodiment, step 2 specifically comprises the following steps:
[0018] S1 Melting Os by induction melting 50 B 50 Alloy: Put the boron nitride crucible containing Os metal raw material and B elemental raw material into the vacuum induction melting furnace and evacuate to a vacuum degree of ≤3.0×10 -2 Pa, fill with 0.05MPa high-purity Ar gas; under Ar gas protection, smelt at 1000-2000℃ for 3-15min, repeat smelting 2-5 times, and take out after cooling;
[0019] S2 will induction smelting Os 50 B 50 The alloy ingot is placed in a vacuum arc furnace, and Os and M elements are added according to the designed proportion of the alloy composition. The vacuum is evacuated to a vacuum degree of ≤8×10 -3 Pa, filled with 0.05MPa high-purity Ar gas; under the protection of Ar gas, use 2000℃~3000℃ arc melting for 3~15min, repeat the melting 5 times, take out after cooling, and prepare the master alloy.
[0020] Due to the anisotropy of thermal expansion of the B single substance raw material, direct vacuum arc melting will cause B to spatter, resulting in the alloy composition of the melt not being consistent with the nominal composition. Therefore, in the present invention, the B element is first melted together with other metal elements (Os).
[0021] In a preferred embodiment, the melt spinning method in step 3 specifically includes:
[0022] The master alloy obtained in step 2 is placed in a rapid solidification induction furnace and evacuated to a vacuum degree of ≤1×10- 2Pa, filled with 0.05MPa high-purity Ar gas, and heated to 1800-2000°C. The speed of the rapid solidification copper wheel was adjusted to 1000-3000r / min, the spray pressure was 0.01-0.02MPa, and after induction heating to melt it for 10s-60s, it was sprayed on the surface of the high-speed rotating copper wheel to obtain an Os-based amorphous alloy thin strip.
[0023] In a preferred embodiment, after step 2 and before step 3, a rapid screening and verification of alloy components with glass-forming ability is further included, which specifically includes the following steps:
[0024] The master alloy ingot obtained in step 2 is cut into thin slices with a thickness of 3 mm, and the surface of the thin slices is treated by laser melting and quenching technology to obtain an Os-based high-temperature amorphous alloy remelting layer; the remelting layer is subjected to phase analysis, and the result shows that the remelting layer has a broadened diffuse diffraction peak, that is, it has a certain glass forming ability;
[0025] Preferably, the laser melting and quenching technology for thin-sheet surface treatment specifically includes:
[0026] The master alloy ingot uniformly melted by induction melting and arc melting is cut to obtain a plane with two parallel sides of 3mm thickness. After grinding and polishing the wire cutting marks, it is ensured that there is no oxide layer on the surface of the master alloy sample and it has a metallic luster. The polished sample is placed on the laser processing table, and the workbench is protected by high-purity Ar gas. The laser type is pulsed laser, laser power 220W, loading voltage 60V, frequency 15Hz, pulse interval 1ms, path spacing 0.2mm, laser moving rate 180mm / min.
[0027] In the present invention, the mother alloy ingot is cut into thin slice samples, and the surface is treated by laser melting and quenching technology to obtain an Os-based high-temperature amorphous alloy remelting layer, which can quickly verify the mother alloy composition that forms the amorphous structure. The confirmation result is that the remelting layer has a broadened diffuse diffraction peak, which indicates that it has a certain glass forming ability. This step can quickly screen and verify the alloy components with glass forming ability through mother alloy melting, laser melting and quenching surface processing, and XRD phase testing, which has the advantages of saving raw materials and fast component development speed, and is far superior to the traditional amorphous alloy development method in terms of development efficiency and resource utilization.
[0028] Compared with the prior art, the technical solution of the present invention has the following advantages:
[0029] The present invention uses high modulus element Os as the main alloy component, uses small atomic element B as the second element, and also includes at least one of Zr, Hf, V, Ta, and W elements for composition design; then uses induction melting or arc melting to melt the corresponding composition of the master alloy ingot; finally, the master alloy ingot is used to prepare an amorphous alloy, and the Os-based high-temperature amorphous alloy thin strip or block is obtained by melt spinning or copper mold casting. After obtaining the master alloy ingot, the amorphous structure of the material can be quickly verified by laser melting and quenching surface processing and XRD phase testing to further improve the development efficiency.
[0030] The Os-based high-temperature amorphous alloy material prepared by the present invention has the characteristics of multiple components and a wide range of components, and can adjust the components of each component in a wide range, which is conducive to industrial application. Moreover, the Os-based high-temperature amorphous alloy material prepared by the present invention has the highest elastic modulus, the highest Vickers microhardness, the highest glass transition temperature, the highest room temperature compression fracture strength and the highest compression fracture strength at 1000K among the existing high-temperature bulk amorphous alloys. Due to its excellent room temperature and high temperature mechanical properties, it can be widely used in the field of precision glass molding mold materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] These and / or other aspects and advantages of the present invention will become more clear and easier to understand from the following detailed description of the embodiments of the present invention in conjunction with the accompanying drawings, in which:
[0032] Figure 1 is Os in Example 1 of the present invention 46 B 38 Hf 16 XRD pattern of alloy slice after laser remelting;
[0033] Figure 2 is Os in Example 1 of the present invention 46 B 38 Hf 16 XRD pattern of 1mm sample of amorphous alloy;
[0034] Figure 3 is Os in Example 1 of the present invention 46 B 38 Hf 16 DSC curve of 1mm sample of amorphous alloy;
[0035] Figure 4 is Os in Example 1 of the present invention 46 B 38 Hf 16 Compression curves of 1 mm sample of amorphous alloy at room temperature and 1000K;
[0036] Figure 5 is Os in Example 2 of the present invention45 B 35 Zr 20 , Os 45 B 35 V 20 , Os 50 B 35 Ta 15 and Os 45 B 35 W 20 XRD pattern of alloy slice after laser remelting;
[0037] Figure 6 is Os in Example 2 of the present invention 45 B 35 Zr 20 , Os 45 B 35 V 20 , Os 50 B 35 Ta 15 and Os 45 B 35 W 20 XRD pattern of amorphous alloy strip sample. DETAILED DESCRIPTION
[0038] In order to enable those skilled in the art to better understand the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific implementation methods, but it should be understood that the protection scope of the present invention is not limited to the specific implementation methods.
[0039] The technical solution of the present application is described in detail below through specific embodiments:
[0040] Unless otherwise specified, the technical means used in the present invention are conventional means well known to those skilled in the art, and the various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods. The reagents used in the present invention are analytically pure unless otherwise specified. The purity of the single element used in the present invention is ≥99.95%.
[0041] Embodiment 1:
[0042] Step 1: Os a B b M c Alloy composition design, M element is Hf element, specific atomic ratio of each element is Os 46 B 38 Hf 16 .
[0043] Step 2: Follow the above designed Os 46 B 38 Hf 16Alloy, according to the atomic ratio and relative atomic mass of each element, calculate the mass of each element required to make 3g of alloy. First, melt Os 50 B 50 Alloy, vacuum degree before melting is 8×10 -3 Pa, Ar was filled as a protective atmosphere during the smelting process, the smelting temperature was 1800℃ for 3 minutes, and the smelting was repeated 5 times to ensure the uniformity of the alloy composition.
[0044] Then the smelted Os 50 B 50 The alloy and Os and Hf elements are melted into a master alloy ingot with a pre-designed composition in a vacuum arc furnace. The vacuum degree is drawn to 8×10 -3 Pa, Ar was filled as a protective atmosphere during the smelting process, the smelting temperature was 2500℃ for 3 minutes, and the smelting was repeated 5 times to ensure the uniformity of the alloy composition.
[0045] The uniformly smelted master alloy obtained in step 2 was cut into alloy slices with a thickness of 3 mm by mechanical processing, and the alloy slices were polished and laser remelted by pulse laser. The laser power used in the laser remelting process was 220 W, the scanning speed was 180 mm / min, and the process was carried out in an Ar atmosphere to obtain Os 46 Hf 16 B 38 The remelted layer of the laser remelted layer is a high-temperature amorphous alloy. XRD is used to analyze the phase of the remelted layer. The XRD scanning speed is 6° / min and the scanning range is 20°-80°. The XRD diagram of the laser remelted layer is as follows: Figure 1 As shown, it can be seen that Os 46 B 38 Hf 16 The alloy has a broadened diffuse diffraction peak in the laser remelted layer, indicating that the alloy has a certain glass-forming ability.
[0046] Step 3: Heat and melt the alloy ingot obtained in step 2 in a protective atmosphere, and spray-cast it into a copper mold to obtain a 1 mm Os-based high-temperature amorphous alloy block. The specific conditions of the copper mold casting method used include: evacuating to a vacuum degree of 1×10 -2 Pa, filled with 0.05MPa high-purity Ar gas, heated to 2000°C. Spray pressure 0.02MPa, induction heating to melt for 30s, sprayed into a copper mold 1mm, and obtained.
[0047] The performance of the Os-based high temperature amorphous alloy block prepared in Example 1 was tested, and the results are as follows:
[0048] XRD was used to characterize the 1 mm Os 46 B 38 Hf 16Phase analysis of amorphous alloy bulk was performed with XRD scanning speed of 6° / min and scanning range of 20°-80°. Figure 2 As described above, it can be seen from the figure that the XRD spectrum shows an obvious broadened diffuse scattering peak, and no other crystal diffraction peaks appear, indicating that the prepared blocks are all completely amorphous structures.
[0049] The prepared 1 mm Os 46 B 38 Hf 16 Thermal properties of amorphous alloys, heating rate 20K / min, test sample mass 20mg. Figure 3 Its glass transition temperature T g is 1231K, and the crystallization starting temperature T x The density ρ measured by Archimedes drainage method is 16.48 g / cm 3 . Microhardness Hv 0.2 The elastic modulus E is 299 GPa, the shear modulus G is 112 GPa, and the bulk modulus B is 303 GPa. The specific data are shown in Table 1. The room temperature and high temperature compression performance curves are shown in Figure 4 As shown, the room temperature fracture strength is 6.8 GPa and the compressive yield strength at 1000 K is 3.9 GPa.
[0050] Table 1 Os 46 B 38 Hf 16 Amorphous alloy 1mm sample performance table
[0051]
[0052] Example 2
[0053] Step 1: Os a B b M c In the alloy composition design, the M elements are Zr, V, Ta and W, and the specific atomic ratio of each element is Os 45 B 35 Zr 20 , Os 45 B 35 V 20 , Os 50 B 35 Ta 15 and Os 45 B 35 W 20 .
[0054] Step 2: Follow the above designed Os 45 B35 Zr 20 , Os 45 B 35 V 20 , Os 50 B 35 Ta 15 and Os 45 B 35 W 20 Alloy, according to the atomic ratio and relative atomic mass of each element, calculate the mass of each element required to make 3g of alloy. First, melt Os 50 B 50 Alloy, vacuum degree before melting is 8×10 -3 Pa, Ar was filled as a protective atmosphere during the smelting process, and the smelting temperature was 1800℃ for 3 minutes, and the smelting was repeated 5 times to ensure that the alloy composition was uniform. 50 B 50 The alloy and the single elements of Os, V, Ta, and W are melted into a master alloy ingot with a pre-designed composition in a vacuum arc furnace. The vacuum degree is drawn to 8×10 - 3 Pa, Ar was filled as a protective atmosphere during the smelting process, the smelting temperature was 2500℃ for 3 minutes, and the smelting was repeated 5 times to ensure the uniformity of the alloy composition.
[0055] The uniformly smelted master alloy obtained in step 2 was cut into alloy slices with a thickness of 3 mm by mechanical processing, and the alloy slices were polished and laser remelted by pulse laser. The laser power used in the laser remelting process was 220 W, the scanning speed was 180 mm / min, and the process was carried out in an Ar atmosphere to obtain Os 45 B 35 Zr 20 , Os 45 B 35 V 20 , Os 50 B 35 Ta 15 and Os 45 B 35 W 20 High temperature amorphous alloy remelting layer. XRD is used to analyze the phase of the remelting layer. The XRD scanning speed is 6° / min and the scanning range is 20°-80°. The XRD diagram of the laser remelting layer is as follows: Figure 5 As shown in the figure, it can be seen that the remelted layer has a broadened diffuse diffraction peak, indicating that the above alloy has a certain glass forming ability.
[0056] Step 3: The alloy ingot obtained in step 2 is heated and melted in a protective atmosphere, and an Os with a thickness of 30 μm is obtained by melt spinning method. 45 B35 Zr 20 , Os 45 B 35 V 20 , Os 50 B 35 Ta 15 The specific reaction conditions of the melt spinning method include: evacuating to a vacuum degree of 1×10 -2 Pa, filled with 0.05MPa high-purity Ar gas, and heated to 2000°C. Adjust the speed of the fast solidification copper wheel to 3000r / min, the spray pressure to 0.02MPa, melt it by induction heating for 30s, and then spray it on the surface of the high-speed rotating copper wheel to obtain it.
[0057] The Os prepared in Example 2 45 B 35 Zr 20 , Os 45 B 35 V 20 , Os 50 B 35 Ta 15 The performance of high temperature amorphous alloy ribbon was tested, and the results are as follows:
[0058] XRD was used to characterize the Os 45 B 35 Zr 20 , Os 45 B 35 V 20 , Os 50 B 35 Ta 15 and Os 45 B 35 W 20 Phase analysis of amorphous alloy strips was performed with XRD scanning speed of 6° / min and scanning range of 20°-80°. Figure 6 As described above, it can be seen from the figure that the XRD spectrum shows an obvious broadened diffuse scattering peak, and no other crystal diffraction peaks appear, indicating that the prepared blocks are all completely amorphous structures.
[0059] Differential scanning calorimetry (DSC) was used to analyze the prepared Os 45 B 35 Zr 20 , Os 45 B 35 V 20 , Os 50 B 35 Ta 15 and Os 45 B 35 W 20Thermal properties of amorphous alloy strip samples, the test sample mass is 20 mg, the heating rate is 20 K / min. The density ρ is measured using the Archimedean drainage method. The microhardness Hv is tested using a Vickers microhardness tester 0.2 The above performance data are shown in Table 2.
[0060] Table 2 Os 45 B 35 Zr 20 , Os 45 B 35 V 20 , Os 50 B 35 Ta 15 and Os 45 B 35 W 20 Amorphous alloy strip sample performance table
[0061]
[0062] It can be seen from the table that Os 45 B 35 Zr 20 Glass transition temperature T g is 1283K, and its microhardness is Hv 0.2 As high as 18.44GPa.
[0063] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.
Claims
1. An Os-based high-temperature amorphous alloy material, characterized in that: The chemical formula of the Os-based high temperature amorphous alloy material is Os a B b M c ; Wherein, the element M includes at least one of Zr, Hf, V, Ta and W; a, b and c are the atomic percentages of the corresponding elements, a=39-50, b=34-44, c=12-24, and the sum of the atomic percentages of each element is a+b+c=100.
2. The Os-based high temperature amorphous alloy material according to claim 1, characterized in that: The glass transition temperature of the Os-based high-temperature amorphous alloy material is 1040K-1283K.
3. The Os-based high temperature amorphous alloy material according to claim 1, characterized in that: The Vickers microhardness value of the Os-based high-temperature amorphous alloy material is above 16.74 GPa.
4. The Os-based high temperature amorphous alloy material according to claim 1, characterized in that: In the Os-based high-temperature amorphous alloy material, when the M element is the Hf element, the atomic percentages of the elements are respectively a=42-50, b=34-42, c=12-20, and a+b+c=100.
5. The Os-based high temperature amorphous alloy material according to claim 4, characterized in that: The Os a B b Hf c The glass transition temperature of the high temperature amorphous alloy material is 1231K and the Vickers microhardness is 18.06GPa.
6. The Os-based high temperature amorphous alloy material according to claim 4, characterized in that: The Os a B b Hf c The Young's modulus of the high-temperature amorphous alloy material is 299 GPa, the compressive fracture strength at room temperature is 6.8 GPa, and the compressive yield strength at 1000K is 3.9 GPa.
7. The Os-based high temperature amorphous alloy material according to claim 1, characterized in that: The Os-based high temperature amorphous alloy composition includes Os 45 B 35 Zr 20 , Os 45 B 35 V 20 , Os 50 B 35 Ta 15 and Os 45 B 35 W 20 .
8. The method for preparing the Os-based high temperature amorphous alloy material according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1: According to the chemical formula of the Os-based high temperature amorphous alloy, Os a B b M c Calculate the mass ratio of each element and weigh and mix the ingredients; the element M includes at least one of Zr, Hf, V, Ta and W; a, b and c are the atomic percentages of the corresponding elements, a=39-50, b=34-44, c=12-24, and the sum of the atomic percentages of the elements is a+b+c=100; Step 2: using an induction melting method to melt each element into a master alloy ingot; Step 3: Heat and melt the master alloy ingot obtained in step 2 in a protective atmosphere, and prepare an Os-based high-temperature amorphous alloy strip by melt spinning; or heat and melt the master alloy ingot obtained in step 2 in a protective atmosphere, and prepare an Os-based high-temperature amorphous alloy block by copper mold casting.
9. The method for preparing the Os-based high temperature amorphous alloy material according to claim 8, characterized in that: After step 2, the process also includes rapid screening and verification of alloy components with glass-forming ability, which specifically includes the following steps: The master alloy ingot obtained in step 2 is cut into thin slices with a thickness of 3 mm, and the surface of the thin slices is treated by laser melting and quenching technology to obtain an Os-based high-temperature amorphous alloy remelted layer; the remelted layer is subjected to phase analysis, and the result shows that the remelted layer has a broadened diffuse diffraction peak, that is, it has a certain glass-forming ability.
Citation Information
Patent Citations
High-entropy amorphous alloy material and preparation method thereof
CN103334065A
Platinum-based bulk amorphous alloy and preparation method thereof
CN104372266A
Amorphous alloy with ultrahigh initial crystallization temperature and preparation method thereof
CN111363987A
High strength amorphous alloy and its production
JP1999071661A
Mo-BASED HEAT-RESISTANT AMORPHOUS ALLOY
JP2006348333A